General anesthesia for caesarean section. Issue 3 (June 2015) - Devroe, Sarah; Van de Velde, Marc; Rex, Steffen
Abstract : Purpose of review: For most anaesthesiologists, the clinical experience with general anaesthesia for caesarean section is very low. General anaesthesia is mostly performed for emergency grade 1 caesarean section and due to a lack of time to apply a neuraxial anaesthesia technique. Unfortunately, the majority of anaesthesiologists rely on historical and partly outdated approaches in this stressful situation. We propose an evidence-based approach to general anaesthesia for caesarean section. Recent findings: Rapid sequence induction using propofol and rocuronium should become the standard for general anaesthesia in the obstetric patient. Short-acting opioids are still not given routinely but should never be withheld in case of severe preeclampsia. Cricoid pressure can only be accurately performed by trained caregivers and should be released if intubation appears to be difficult. Supra-glottic airway devices may safely be used in fasted, nonobese elective caesarean section, but endotracheal intubation remains the gold standard, especially in emergency caesarean section in labouring women. Both sevoflurane and propofol are appropriate for the maintenance of general anaesthesia during caesarean section. Awareness remains a major concern in obstetric anaesthesia. Summary: We present a review of recent evidence on general anaesthesia for caesarean section.